On a Markov game with incomplete information - Johannes Hörner; Dinah Rosenberg; Eilon Solan; Nicolas Vieille (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
We consider an example of a Markov game with lack of information on one side, that was .rst introduced by Renault (2002). We compute both the value and optimal strategies for a range of parameter values.
Keywords: 330; Spieltheorie; Markovscher Prozess; Unvollkommene Information; Theorie